Clinical efficacy of photodynamic therapy and laser irradiation as an adjunct to open flap debridement in the treatment of chronic periodontitis: A systematic review and meta‐analysis. Issue 1 (22nd August 2019) - Akram, Zohaib; Shafqat, Syed Saad; Niaz, Muhammad Omar; Raza, Anam; Naseem, Mustafa
Abstract: Background: The aim of this systematic review and meta‐analyses was to assess the quality of evidence and efficacy of antimicrobial photodynamic therapy (aPDT) and laser irradiation (LI) as an adjunct to open flap debridement (OFD) in the treatment of chronic periodontitis. Methods: Electronic searches were conducted in databases (MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Cochrane Oral Health Group Trials Register databases) up to March 2019. Randomized clinical trials (RCTs) comparing clinical efficacy of either aPDT and/or LI, placebo, or no treatment were included. Primary outcomes included clinical attachment level (CAL), while secondary outcomes were reduction in probing depth (PD) and gingival recession (GR) depth. The weighted mean differences (WMD) of outcomes and 95% confidence intervals (CI) for each variable were calculated using random effect model. Results: Six RCTs were included. For aPDT studies, the overall mean difference for CAL gain (WMD = −0.61, 95% CI = −1.22 to −0.016, P  = .044) and PD reduction (WMD = −1.79, 95% CI = −3.44 to −0.14, P  = .034) was significant between aPDT and OFD groups at follow‐up. No significant overall mean difference was observed for GR depth (WMD = 0.02, 95% CI = −0.75 to 0.79, P  = .95). For LI studies, none of the clinical periodontal parameters including CAL gain (WMD = 0.23, 95% CI = −0.09 to 0.55, P  = .159, Figure 3A), PD reduction (WMD = 0.31, 95% CI = −0.67 to 1.31, P  = .52, Figure 3B) and GR depth (WMD = −0.34, 95% CI = −2.47 to 1.78, P  = .74, Figure 3C) were found to be significant between LI and OFD groups at follow‐up. Conclusion: With the limited data available, only aPDT as an adjunct to OFD showed superior results for clinical periodontal parameters compared to OFD alone in the treatment of chronic periodontitis. Further RCTs are warranted in order to obtain robust conclusions with regard to laser therapy.